Horace Saint-Paul: A Young British Nobleman in the Service of Austria during the Seven Years’ War - Monseigne, Clément (Historical Studies on Central Europe, 2024)
This article examines the singular destiny of Horace Saint-Paul, a young British nobleman who served in the Imperial Army during the Seven Years’ War. While the entry of foreign nobles into the service of another nation is not surprising in the modern era, the case of Saint-Paul is particularly interesting to study because of his lightning ascension through the ranks. He managed to rise to a senior position in the general staff without any military experience. His entry into the service of an army that was part of a coalition opposed to his homeland also raises questions about the complex relationship between patriotism and cosmopolitanism in the mid-eighteenth century. His example clearly illustrates the great adaptability of the nobility in the Age of Enlightenment, for whom the context of war provided significant opportunities to move around Europe.